Performance-improved Li-O2 batteries by tailoring the phases of MoxC porous nanorods as an efficient cathode - Yu, Hong (2020)
Novel nitrogen-doped porous molybdenum carbide (α-MoC1−x and β-Mo2C) architectures were prepared using Mo-based metal–organic frameworks (MOFs) as the precursor. The synthesized molybdenum carbides consist of numerous nanocrystals organized into micro-sized rods with interpenetrating mesoporous-channels and macroporous-tunnels along the axial direction. When employed as the cathode catalyst for Li-O2 batteries, this dual pore configuration offers abundant active sites for the electrochemical reaction and many nucleation sites for the discharge product of Li2O2; hence, decent performances were obtained. Among the two synthesized molybdenum carbides, the α-MoC1−x electrode stands out as being better due to its lower charge transfer resistance (395.8 Ω compared to 627.9 Ω) and better O2 adsorption (binding energy of −1.87 eV of α-(111)-Mo compared to −0.72 eV of β-(101)-Mo). It delivered a high full discharge of 20 212 mA h g−1 with a discharge voltage of 2.62 V at 200 mA g−1. A good cycling stability was also obtained: i.e. 100 stable cycles with a fixed capacity of 1000 mA h g−1 (at a current density of 200 mA g−1) with a charging voltage of 4.24 V and maintaining a respectable round-trip efficiency of ∼70%.